Association between social activity frequency and overall survival in older people: results from the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Issue 5 (6th March 2023) - Wang, Ziqiong; Zheng, Yi; Ruan, Haiyan; Li, Liying; Duan, Linjia; He, Sen
Abstract : Background: This study aimed to explore the impact of social activity frequency on mid- and long-term overall survival in older Chinese people. Methods: The association between social activity frequency and overall survival was analysed in 28 563 subjects from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) cohorts. Results: A total of 21 161 (74.1%) subjects died during the follow-up of 132 558.6 person-years. Overall, more frequent social activity was associated with longer overall survival. From baseline to 5 years of follow-up, adjusted time ratios (TRs) for overall survival were 1.42 (95% CI 1.21 to 1.66, p<0.001) in the not monthly but sometimes group, 1.48 (95% CI 1.18 to 1.84, p=0.001) in the not weekly but at least once/month group, 2.10 (95% CI 1.63 to 2.69, p<0.001) in the not daily but at least once/week group, and 1.87 (95% CI 1.44 to 2.42, p<0.001) in the almost everyday group versus never group. From 5 years to the end of follow-up, adjusted TRs for overall survival were 1.05 (95% CI 0.74 to 1.50, p=0.766) in the not monthly but sometimes group, 1.64 (95% CI 1.01 to 2.65, p=0.046) in the not weekly but at least once/month group, 1.23 (95% CI 0.73 to 2.07, p=0.434) in the not daily but at least once/week group, and 3.04 (95% CI 1.69 to 5.47, p<0.001) in the almost everyday group versus the never group. Stratified and sensitivity analysis revealed similar results. Conclusion: Frequent participation in social activity was significantly associated with prolonged overall survival in older people. However, only participating in social activity almost every day could significantly prolong long-term survival.